RESEARCH AND DEVELOPMENT: AS THE PRIMARY ALTERNATIVE TO EDUCATIONAL RESEARCH DESIGN FRAMEWORKS - Umar Umar; M Bambang Purwanto; Moch. Malik Al Firdaus (STIBA IEC JAKARTA, 2023)
A model for better educational practices is being developed as a result of the expansion of educational research as a branch of science, according to the researchers working in this area. Research and Development (R&D) Method is one of the best model designs. This study employs a descriptive qualitative research methodology that depicts the scenario as it relates to an indicator or the current status of the findings in the field. In this study, the methods for gathering data and information were interviewing, and documenting studies of the necessary data sources. This article presents a number of models for development research, including the Borg and Gall Development model, the Sadiman Development model, the ADDIE Development model, the Dick and Carey Development model, and the Data Center for Education and Culture Information Technology of Ministry of National Education